Geopolitical Implications and the Importance of Climate Change on the Emergence of Russia’s Northern Sea Route (NSR) - Sastrawiguna, Cakra Tri; Nugraha, Imam Fadhil (Triwikrama: Jurnal Ilmu Sosial, 2024)
Accelerated Arctic ice melting due to climate change has transformed the region into a focal point of global interest, particularly in trade and geopolitics. A notable development is the emergence of the Northern Sea Route (NSR), offering a shorter alternative to traditional routes like the Suez Canal. This study examines the economic potential, geopolitical challenges, and environmental impacts of the NSR's development. Using a qualitative methodology, it incorporates literature reviews, policy analysis, and geopolitical theories such as Mackinder's Heartland Theory. The findings indicate that Russia leverages the NSR as a strategic component of its Arctic policy, enforcing strict legal controls and advancing infrastructure development. However, key challenges include sovereignty disputes with Western nations, infrastructural limitations, and significant environmental risks. Despite its promise of reduced shipping distances and costs, skepticism remains about the NSR's viability as a global trade corridor. The paper underscores the need for a balance between economic development, environmental protection, and geopolitical stability to ensure the NSR's sustainability. Thus, the NSR represents not only an economic opportunity but also a reflection of broader global dynamics, positioning it as a strategic area requiring international attention and cooperation.